New Aspects of Bioethanol One-step Catalytic Conversion to Fuel Components - A. Chistyakov; M. Tsodikov; M. Chudakova; A. Gekhman; I. Moiseev; F. Luk (Chemical Engineering Transactions, 2011)
Abstract preview not available - see full-text PDF article.